Tax declared unconstitutional after the tax execution has been filed: PIS contribution. Declaration of unconstitutionality of Decree-Laws no. 2.445/88 e 2.449/88. Issue of Resolution 49/95. Effects “erga omnes” and ‘ex tunc’ effects. Need for a new launch within the decadence period. (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The issue at hand is to analyze the effects that the declaration of formal unconstitutionality of a tax, with “erga omnes” effects, attributed by a resolution issued by the Federal Senate, will have on a previously filed tax execution, with the legal basis erected for the collection of the taxes that are the subject of this execution being exactly the rule that was declared unconstitutional due to a procedural defect. Detailing the problem even further, what would be the effects of this declaration of formal unconstitutionality on this collection, by means of a tax execution, which is already underway, in relation to the tax credit, which until then had been perfectly enforceable, since it had been duly constituted?
Keywords: tax×inconstitutionality×tax enforcement×resolution of the Federal Senate×effect “erga omnes” and “ex tunc”×new entry×decay period×PIS×; tax; inconstitutionality; tax enforcement; resolution of the Federal Senate; effect; new entry; decay period; PIS